2019
DOI: 10.15252/emmm.201910923
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐mediated ECM depletion improves tumour perfusion and payload delivery

Abstract: High extracellular matrix (ECM) content in solid cancers impairs tumour perfusion and thus access of imaging and therapeutic agents. We have devised a new approach to degrade tumour ECM, which improves uptake of circulating compounds. We target the immune‐modulating cytokine, tumour necrosis factor alpha (TNFα), to tumours using a newly discovered peptide ligand referred to as CSG. This peptide binds to laminin–nidogen complexes in the ECM of mouse and human carcinomas with little or no peptide detected in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 58 publications
6
31
0
Order By: Relevance
“…Using cytokine profiling, we demonstrated that PFD significantly depleted the secretion of cancer-and invasion-promoting cytokines, particularly IL8, CCL17, and TNF-β. Many studies highlighted the critical role of these factors in the interaction of the carcinomastromal cell and ECM deposition toward the induction of an invasive TME and activation of EMT and stemness [6,7,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Using cytokine profiling, we demonstrated that PFD significantly depleted the secretion of cancer-and invasion-promoting cytokines, particularly IL8, CCL17, and TNF-β. Many studies highlighted the critical role of these factors in the interaction of the carcinomastromal cell and ECM deposition toward the induction of an invasive TME and activation of EMT and stemness [6,7,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported the discovery of a peptide, CSG (CSGRRSSKC) that binds specifically to the laminin-nidogen-1 complex of the ECM in mouse and human breast, pancreas and liver tumours [49]. We have shown that CSG fused to a cytokine, TNFα, acts as a delivery agent allowing for specific binding of TNFα to tumour ECM, triggering effective immune-mediated anti-tumour effects [49].…”
Section: Introductionmentioning
confidence: 99%
“…Large number of such molecules carry either anti-or pro-inflammatory protein in hopes of deciphering immune response [32,[78][79][80][81][82][83][84]. Recently, a homing peptide targeting tumor ECM delivered tumor necrosis factor-α (TNFα) to ECM rich regions in tumors and caused immune cell infiltration and subsequent immune cell-induced ECM breakage [79]. Theoretically, similar approaches inducing "immunological reaction towards connective tissue" could be applied to situations where scarring or fibrosis has ensued, and the breakage of the fibrosis is desirable without side effects in the rest of the body.…”
Section: Systemically Administered Anti-fibrotic Molecule Car-decorinmentioning
confidence: 99%